Wasatiyyah and Islamic Values in Reinforcing Malay Muslim Ethnic Relations: A Case Study of Thai Wasatiyyah Institute for Peace and Development in Thailand - Dorloh, Sulaiman; Yusuf, Kamarussalam Bin (UIN Sunan Gunung Djati Bandung, 2015)
The Wasatiyyah or moderation Institute for Peace and Development was initiated by the current Chularajmontri, Aziz Pithakkompon on 21th August 2014, with the aims of fostering harmony among the diverse ethnics in the country and providing a counter-balance to extremism and extremist as it is taking place in various parts of the world and promoting moderation and peace among Muslims in Thai society. The concept of wasatiyyah or moderation is appropriate to be highlighted and practiced in Thai society to curb extremist activities in all matters. Even though some negative perceptions were voiced by a few parties, but the actual intentions could result in a decline of racial strains, as being moderate has been the practice of the Malay community and its leaders for ages. In fact, this approach has contributed to the success of the Malay community in the Deep South in securing the Malay indentity from their Buddhist neighburs in the country, without having to resort to spilling a lot of blood. Based on previous research, it was observed that the concept of wasatiyyah had a great influence on the Malays, as it had a strong link with the Islamic values that have been embedded in the Malay community. The Islamic values are the main elements that shape the Malaysâ conduct, and it is the results of interaction with social norms, for it has bred certain social values that include compromise, modesty, respect and cooperation as transpired when Malays interact among themselves or with other communities. The main goal for the institution to maintain peace and harmony in the society. Based on textual analysis, the study determines that the concept of wasatiyyah concept or moderation is part of the social values borne out of the Malaysâ values based on Islamic teachings. Hence, the question is, to what extent does the wasatiyyah concept implemented in the institute. In order to answer the question above, this study has set two main objectives. First, to identify the wasatiyyah concept in Islamic law; and second, to analyse its implementation in the institude. The qualitative study in the form of exploratory and descriptive approach used the content analysis method. The content analysis method was used to identify and analyse the wasatiyyah concept in Islamic law and also to analyse the implementation of the wasatiyyah concept in the institute.